Pengaruh Model Pembelajaran Discovery Learning Berbasis Tri Kaya Parisudha terhadap Sikap Sosial dan Kemampuan Berpikir Kritis Siswa - Yudiana, Kadek; M.Pd., I Made Hendra Sukmayasa (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sarjanawiyata Tamansiswa, 2025)
The aim of this research is to examine the influence of the Tri Kaya Parisudha-based discovery learning model on the social attitudes and critical thinking abilities of the science and science subjects of class V students at SD N 4 Banyuasri, both individually and simultaneously. This research is experimental research with a research design, namely One Group Pretest-Posttest Design. The population which is also the sample in this research is the fifth grade students of SD N 4 Banyuasri, totaling 30 students. The independent variable in this research is a discovery learning model based on Tri Kaya Parisudha. Meanwhile, the dependent variables in this research are students' social attitudes and critical thinking abilities. The data collection methods used are observation methods and test methods. The observation method is used to measure social attitudes, while the test method is used to measure students' critical thinking abilities. The data analysis methods used in this research are descriptive data analysis methods and inferential data analysis methods. Descriptive data analysis was carried out to find the mean, median, mode, standard deviation, variance and category of each variable. Meanwhile, the inferential data analysis method uses MANOVA data analysis. Based on the research that has been conducted, it is concluded that there is a significant influence of the Tri Kaya Parisudha-based discovery learning model on the social attitudes and critical thinking abilities of the science and science subjects of class V students at SD N 4 Banyuasri, both individually and simultaneously.